Experimental and theoretical investigation of the complexation of 5-methyl-7-isobutyl-1, 2, 4-triazolo[1, 5-a]pyrimidine with platinum(ii) ions. (7th July 2017) - Łakomska, Iwona; Babinska, Magdalena; Wojtczak, Andrzej; Kozakiewicz, Anna; Sitkowski, Jerzy; Jarzęcki, Andrzej A.
Abstract : Dichlorido platinum(ii ) complexes with 5-methyl-7-isobutyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (ibmtp) were synthesized and characterized by various tools: IR, 1 H, 13 C, 15 N, 195 Pt NMR and DFT calculations. Abstract : In this joint experimental–theoretical work, the crystal structures of 5-methyl-7-isobutyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (ibmtp) (1 ) and its three mononuclear chlorido platinum(ii ) complexes, cis -[PtCl2 (ibmtp)2 ] (2 ), cis -[PtCl2 (dmso)(ibmtp)] (3 ), and cis -[PtCl2 (ibmtp)(NH3 )] (4 ), have been determined. The structures of the compounds (1–4 ) have been supported by X-ray, IR and multinuclear 1 H, 13 C, 15 N and 195 Pt NMR spectroscopy along with density functional theory (DFT) calculations. In complex (2 ) the coordination sphere of Pt(ii ) consists of two monodentate ibmtp ligands and two cis chlorido ions. However, in complexes (3 ) and (4 ) with a single ibmtp ligand and two cis chlorido ions, the square planar geometry around Pt(ii ) is completed by either dmso or ammonia ligands, respectively. This is supported by DFT calculations which show good agreement with the experimental data. Notably, DFT calculations allow us to suggest that compound (3 ) in the presence of dimethylformamide undergoes a slow cis – trans isomerization. In addition, compounds (2–4 ) have been tested for in vitro cytotoxic activity against three human tumor cell lines: T47D (breast cancer), A549 (non-small cell lung carcinoma), and LoVo (colon cancer), and one healthy cell line BALB/3T3 (mouse embryonic fibroblast). The tests indicate that the in vitro cytotoxicity for compounds (2–4 ) strongly correlates with the nature of the non-leaving ligands and the geometry around platinum(ii ).